Fully amino acid-based hydrogel as potential scaffold for cell culturing and drug delivery - Juriga, Dávid; Sipos, Evelin; Hegedűs, Orsolya; Varga, Gábor; Zrínyi, Miklós; Nagy, Krisztina S.; Jedlovszky-Hajdú, Angéla (Beilstein Journal of Nanotechnology, 2019)
Polymer hydrogels are ideal scaffolds for both tissue engineering and drug delivery. A great advantage of poly(amino acid)-based hydrogels is their high similarity to natural proteins. However, their expensive and complicated synthesis often limits their application. The use of poly(aspartic acid) (PASP) seems an appropriate solution for this problem due to the relatively cheap and simple synthesis of PASP. Using amino acids not only as building blocks in the polymer backbone but also as cross-linkers can improve the biocompatibility and the biodegradability of the hydrogel. In this paper, PASP cross-linked with cystamine (CYS) and lysine-methylester (LYS) was introduced as fully amino acid-based polymer hydrogel. Gels were synthesized employing six different ratios of CYS and LYS. The pH dependent swelling degree and the concentration of the elastically active chain were determined. After reduction of the disulfide bonds of CYS, the presence of thiol side groups was also detected. To determine the concentration of the reactive cross-linkers in the hydrogels, a new method based on the examination of the swelling behavior was established. Using metoprolol as a model drug, cell proliferation and drug release kinetics were studied at different LYS contents and in the presence of thiol groups. The optimal ratio of cross-linkers for the proliferation of periodontal ligament cells was found to be 60−80% LYS and 20−40% CYS. The reductive conditions resulted in an increased drug release due to the cleavage of disulfide bridges in the hydrogels. Consequently, these hydrogels provide new possibilities in the fields of both tissue engineering and controlled drug delivery.
Keywords: biocompatibility; cystamine; hydrogel; lysine; poly(amino acid); poly(aspartic acid); polymer

(untitled) - Drury, J. L.; Mooney, D. J. (Biomaterials, 2003)

(untitled) - Fedorovich, N. E.; Alblas, J.; de Wijn, J. R.; Hennink, W. E.; Verbout, A. J.; Dhert, W. J. A. (Tissue Eng., 2007)

(untitled) - Lee, K. Y.; Mooney, D. J. (Chem. Rev., 2001)

(untitled) - Li, J.; Mooney, D. J. (Nat. Rev. Mater., 2016)

(untitled) - Brunner, C. A.; Groner, R. W. (Can. J. Plast. Surg., 2006)

(untitled) - Al-Kinani, A. A.; Zidan, G.; Elsaid, N.; Seyfoddin, A.; Alani, A. W. G.; Alany, R. G. (Adv. Drug Delivery Rev., 2018)

(untitled) - Annabi, N.; Selimović, Š.; Acevedo Cox, J. P.; Ribas, J.; Afshar Bakooshli, M.; Heintze, D.; Weiss, A. S.; Cropek, D.; Khademhosseini, A. (Lab Chip, 2013)

(untitled) - Lu, Y.; Wang, D.; Li, T.; Zhao, X.; Cao, Y.; Yang, H.; Duan, Y. Y. (Biomaterials, 2009)

(untitled) - Cavalcanti, B. N.; Zeitlin, B. D.; Nör, J. E. (Dent. Mater., 2013)

(untitled) - Abdallah, M.; Martin, M.; El Tahchi, M. R.; Balme, S.; Faour, W. H.; Varga, B.; Cloitre, T.; Páll, O.; Cuisinier, F. J. G.; Gergely, C.; Bassil, M. J.; Bechelany, M. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Nair, L. S.; Laurencin, C. T. (Prog. Polym. Sci., 2007)

(untitled) - Duncan, R.; Vicent, M. J. (Adv. Drug Delivery Rev., 2013)

(untitled) - Varga, Z.; Molnár, K.; Torma, V.; Zrínyi, M. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Park, K. (J. Controlled Release, 2014)

(untitled) - Lee, P. I. (J. Controlled Release, 1985)

(untitled) - Brandl, F.; Kastner, F.; Gschwind, R. M.; Blunk, T.; Teßmar, J.; Göpferich, A. (J. Controlled Release, 2010)

(untitled) - Gyarmati, B.; Némethy, Á.; Szilágyi, A. (Eur. Polym. J., 2013)

(untitled) - Kurland, N. E.; Ragland, R. B.; Zhang, A.; Moustafa, M. E.; Kundu, S. C.; Yadavalli, V. K. (Int. J. Biol. Macromol., 2014)

(untitled) - Ahn, S.-k.; Kasi, R. M.; Kim, S.-C.; Sharma, N.; Zhou, Y. (Soft Matter, 2008)

(untitled) - Gupta, P.; Vermani, K.; Garg, S. (Drug Discovery Today, 2002)

(untitled) - Zrinyi, M.; Gyenes, T.; Juriga, D.; Kim, J.-H. (Acta Biomater., 2013)

(untitled) - Gyenes, T.; Torma, V.; Gyarmati, B.; Zrínyi, M. (Acta Biomater., 2008)

(untitled) - Ulery, B. D.; Nair, L. S.; Laurencin, C. T. (J. Polym. Sci., Part B: Polym. Phys., 2011)

(untitled) - Pitarresi, G.; Saiano, F.; Cavallaro, G.; Mandracchia, D.; Palumbo, F. S. (Int. J. Pharm., 2007)

(untitled) - Juriga, D.; Nagy, K.; Jedlovszky-Hajdú, A.; Perczel-Kovách, K.; Chen, Y. M.; Varga, G.; Zrínyi, M. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Park, K. M.; Shin, Y. M.; Kim, K.; Shin, H. (Tissue Eng., Part B, 2018)

(untitled) - Naahidi, S.; Jafari, M.; Logan, M.; Wang, Y.; Yuan, Y.; Bae, H.; Dixon, B.; Chen, P. (Biotechnol. Adv., 2017)

(untitled) - Hu, W.; Ying, M.; Zhang, S.; Wang, J. (J. Biomed. Nanotechnol., 2018)

Science and Principles of Biodegradable and Bioresorbable Medical Polymers - Zhang, X.; Peng, X.; Zhang, S. W. (Biodegradable medical polymers, 2017)

(untitled) - Datta, S.; Barua, R.; Sarkar, R.; Barui, A.; Chowdhury, A. R.; Datta, P. (IOP Conf. Ser.: Mater. Sci. Eng., 2018)

(untitled) - Crompton, K. E.; Goud, J. D.; Bellamkonda, R. V.; Gengenbach, T. R.; Finkelstein, D. I.; Horne, M. K.; Forsythe, J. S. (Biomaterials, 2007)

(untitled) - Matsusaki, M.; Yoshida, H.; Akashi, M. (Biomaterials, 2007)

(untitled) - Manocha, B.; Margaritis, A. (Crit. Rev. Biotechnol., 2008)

(untitled) - Krisch, E.; Gyarmati, B.; Barczikai, D.; Lapeyre, V.; Szilágyi, B. Á.; Ravaine, V.; Szilágyi, A. (Eur. Polym. J., 2018)

(untitled) - Aderibigbe, B. A.; Ray, S. S. (J. Drug Delivery Sci. Technol., 2016)

(untitled) - Kamaly, N.; Yameen, B.; Wu, J.; Farokhzad, O. C. (Chem. Rev., 2016)

(untitled) - Juriga, D.; Laszlo, I.; Ludanyi, K.; Klebovich, I.; Chae, C. H.; Zrinyi, M. (Acta Biomater., 2018)

(untitled) - Molnar, K.; Juriga, D.; Nagy, P. M.; Sinko, K.; Jedlovszky-Hajdu, A.; Zrinyi, M. (Polym. Int., 2014)

(untitled) - Molnar, K.; Jedlovszky-Hajdu, A.; Zrinyi, M.; Jiang, S.; Agarwal, S. (Macromol. Rapid Commun., 2017)

(untitled) - Jedlovszky-Hajdu, A.; Molnar, K.; Nagy, P. M.; Sinko, K.; Zrinyi, M. (Colloids Surf., A, 2016)

(untitled) - Kim, M.; Shin, S. W.; Lim, C. W.; Kim, J.; Um, S. H.; Kim, D. (Biomater. Sci., 2017)

(untitled) - Németh, C.; Gyarmati, B.; Abdullin, T.; László, K.; Szilágyi, A. (Acta Biomater., 2017)

(untitled) - Gong, C.; Lu, C.; Li, B.; Shan, M.; Wu, G. (J. Mater. Sci., 2017)

(untitled) - Yavvari, P. S.; Awasthi, A. K.; Sharma, A.; Bajaj, A.; Srivastava, A. (J. Mater. Chem. B, 2019)

(untitled) - Krisch, E.; Messager, L.; Gyarmati, B.; Ravaine, V.; Szilágyi, A. (Macromol. Mater. Eng., 2016)

(untitled) - Szilágyi, B. Á.; Némethy, Á.; Magyar, A.; Szabó, I.; Bősze, S.; Gyarmati, B.; Szilágyi, A. (React. Funct. Polym., 2018)

(untitled) - Samal, S. K.; Dash, M.; Van Vlierberghe, S.; Kaplan, D. L.; Chiellini, E.; van Blitterswijk, C.; Moroni, L.; Dubruel, P. (Chem. Soc. Rev., 2012)

(untitled) - Seo, B.-M.; Miura, M.; Gronthos, S.; Mark Bartold, P.; Batouli, S.; Brahim, J.; Young, M.; Gehron Robey, P.; Wang, C. Y.; Shi, S. (Lancet, 2004)

(untitled) - Kadar, K.; Kiraly, M.; Porcsalmy, B.; Molnar, B.; Racz, G. Z.; Blazsek, J.; Kallo, K.; Szabo, E. L.; Gera, I.; Gerber, G.; Varga, G. (J. Physiol. Pharmacol., 2009)

(untitled) - Flory, P. J.; Rehner, J., Jr (J. Chem. Phys., 1943)

Fortschritte Der Hochpolymeren-Forschung - Dušek, K.; Prins, W. (Structure and elasticity of non-crystalline polymer networks, 1969)

(untitled) - Osada, Y.; Gong, J. (Prog. Polym. Sci., 1993)

(untitled) - Ricka, J.; Tanaka, T. (Macromolecules, 1984)

(untitled) - Brannon-Peppas, L.; Peppas, N. A. (Chem. Eng. Sci., 1991)

(untitled) - Menzel, C.; Olsson, E.; Plivelic, T. S.; Andersson, R.; Johansson, C.; Kuktaite, R.; Järnström, L.; Koch, K. (Carbohydr. Polym., 2013)

(untitled) - Moe, S. T.; Elgsaeter, A.; Skjåk-Bræk, G.; Smidsrød, O. (Carbohydr. Polym., 1993)

(untitled) - Santos, E.; Hernández, R. M.; Pedraz, J. L.; Orive, G. (Trends Biotechnol., 2012)

(untitled) - Lu, H.; Guo, L.; Kawazoe, N.; Tateishi, T.; Chen, G. (J. Biomater. Sci., Polym. Ed., 2009)

(untitled) - Zheng, S.; Guan, Y.; Yu, H.; Huang, G.; Zheng, C. (New J. Chem., 2019)

(untitled) - Shih, I. L.; Van, Y. T.; Shen, M. H. (Mini-Rev. Med. Chem., 2004)

(untitled) - Tian, W. M.; Hou, S. P.; Ma, J.; Zhang, C. L.; Xu, Q. Y.; Lee, I. S.; Li, H. D.; Spector, M.; Cui, F. Z. (Tissue Eng., 2005)

(untitled) - Ma, L.; Gao, C.; Mao, Z.; Zhou, J.; Shen, J. (J. Biomed. Mater. Res., Part A, 2004)

(untitled) - Liu, S.; Xie, R.; Cai, J.; Wang, L.; Shi, X.; Ren, L.; Wang, Y. (RSC Adv., 2015)